Transformasi Digital: Memudahkan Proses Pemindahbukuan Melalui Aplikasi SIKD Di Kantor Bupati Sleman - Anggun Puspita Anggraeni; Ika Wulandari; Sumaryono Sumaryono (Jurnal Nasional Pengabdian Masyarakat, 2023)
Digital transformation is considered important in improving the efficiency and accuracy of the overbooking process at the Sleman Regent's Office. This article will explain in more detail about the SIKD application, implementation steps, benefits, and impacts of this digital transformation. It will also discuss the challenges and obstacles that may be encountered during the implementation and how to overcome them. It is expected that with this digital transformation, the overbooking process at the Sleman Regent's Office can become easier, faster, and more accurate so as to improve the quality of public services